SISTEM BAGI HASIL DALAM AKAD MUZARA’AH PADA PETANI TEMBAKAU DI SUMBER MALANG SITUBONDO - Misba Huddin; A. Muhyiddin Khotib; Fariro Hasani (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2024)
Plalangan Village is one of the villages where the majority of the livelihood is farming and in which there are many methods used to manage the land owned, ranging from managing it yourself to managing it by other people, one of the contracts used is the muzara'ah contract. The muzara'ah contract is a cooperative agreement between the land owner and the cultivator where the seeds to be planted come from the land owner. The agreement in this contract is usually done verbally without any written agreement with the distribution of the results agreed at the beginning of the agreement, however, in this distribution of results the cultivator is still waiting because the land owner is still looking for buyers who will buy tobacco, so this is the background for this research. . The type of research used is field research, that is, researchers go directly into the field to conduct research so they can see and understand the objects to be discussed. The results of this research show that the profit sharing system in the muzara'ah contract for tobacco farmers in Plalangan Village is that the distribution of the results is agreed upon by both parties at the beginning of the contract. What usually happens is that half is divided for the land owner and the other half for the cultivator, after deducting costs. -cost incurred. Meanwhile, the muzara'ah contract carried out by the people of Plalangan Village, Sumber Malang District, Situbondo Regency is valid because it has fulfilled the pillars and requirements of the muzara'ah contract and is in accordance with the principles of Islamic economics, namely the principle of monotheism, the principle of representation, the principle of justice, the principle of tazkiyah, and the principle of al-falah.